Governance decentralization and local infrastructure provision in Indonesia - Chowdhury, Shyamal; Yamauchi, Futoshi; Dewina, Reno (International Food Policy Research Institute, 2009)
This paper examines the recent decentralization of governance in Indonesia and its impact on local infrastructure provision. The decentralization of decisionmaking power to local jurisdictions in Indonesia may have improved the matching of public infrastructures provision with local preferences. However, decentralization has made local public infrastructures depend on local resources. Due to differences in initial endowments, this may result in the divergence of local public infrastructures in rich and poor jurisdictions. Using data from village-level panel surveys conducted in 1996, 2000, and 2006, this paper finds that (1) local public infrastructures depend on local resources, (2) decentralization has improved the availability of local public infrastructures, (3) local jurisdictions are converging to a similar level of local public infrastructure, and (4) to some extent, decentralized public infrastructures’ provision reflects local preferences.